Expanding the range of drinks in the restaurant business establishments using pectin - Kovalchuk, Svitlana; Nakonechna (Martyniuk), Alina (My University, 2020)
The article discusses the use of pectin in the preparation of functional beverages for restaurants. In connection with the deterioration of the environmental situation in the world and pollution of the environment and food with toxic substances and radionuclides, it is necessary to take preventive measures. This creates the need for humans to take natural detoxifiers and radioprotectors, which include pectin. For the production of fruit juices and drinks, highly esterified pectin can be used. Pectins with a high degree of esterification have a large molecular weight and are able to form gels in an acidic environment. The recommended dosage of pectin in drinks is 0,02–0,25%, depending on the desired taste characteristics. Use of pectin will not only expand the assortment of functional drinks, but will also improve the quality indicators of finished drinks. The use of which normalizes metabolic processes in the body, improves the intestinal microflora, lowers cholesterol, improves blood circulation and helps to eliminate toxic substances and radionuclides.
Keywords: pectin; functional nutrition; drinks; catering; пектин; функціональне харчування; напої; кафедра технології ресторанної і аюрведичної продукції; кафедра готельно-ресторанної справи